2016
DOI: 10.1016/j.biortech.2016.09.083
|View full text |Cite
|
Sign up to set email alerts
|

In-situ biogas upgrading in thermophilic granular UASB reactor: key factors affecting the hydrogen mass transfer rate

Abstract: Biological biogas upgrading coupling CO with external H to form biomethane opens new avenues for sustainable biofuel production. For developing this technology, efficient H to liquid transfer is fundamental. This study proposes an innovative setup for in-situ biogas upgrading converting the CO in the biogas into CH, via hydrogenotrophic methanogenesis. The setup consisted of a granular reactor connected to a separate chamber, where H was injected. Different packing materials (rashig rings and alumina ceramic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 27 publications
3
107
2
1
Order By: Relevance
“…Thus, the aqueous solubility of most gasses is rather low, which limits the gas-liquid mass transfer and hampers the performance of the bioreactor (Tirunehe and Norddahl, 2016). For that reason, the material and type of the module that is used to inject H 2 , the application of gas recirculation flows and the reactor designs are considered as fundamental elements for the implementation of sufficient in-situ biogas upgrading (Bassani et al, 2016). In batch experiments, it was found that the H 2 uptake rate decreased rapidly at CO 2 concentrations < 12% (Agneessens et al, 2017) and the maximum CH 4 content in biogas reached 89% (Mulat et al, 2017).…”
Section: Chemautotrophic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the aqueous solubility of most gasses is rather low, which limits the gas-liquid mass transfer and hampers the performance of the bioreactor (Tirunehe and Norddahl, 2016). For that reason, the material and type of the module that is used to inject H 2 , the application of gas recirculation flows and the reactor designs are considered as fundamental elements for the implementation of sufficient in-situ biogas upgrading (Bassani et al, 2016). In batch experiments, it was found that the H 2 uptake rate decreased rapidly at CO 2 concentrations < 12% (Agneessens et al, 2017) and the maximum CH 4 content in biogas reached 89% (Mulat et al, 2017).…”
Section: Chemautotrophic Methodsmentioning
confidence: 99%
“…In another research performed in upflow anaerobic sludge blanket reactor, hollow fiber membrane was installed in an external degassing unit and the obtained efficiency of the in-situ biogas upgrading reached 94% (Luo et al, 2014). However, as the cost of such membranes has to be considered for full scale applications, other porous devices, such as ceramic sponges, have been proven to benefit the coupling of CO 2 and H 2 and their consequent transformation to CH 4 (Bassani et al, 2016). A comparison of different in-situ configurations is presented in Table 2. 2.2.1.2.…”
Section: Chemautotrophic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grass obtained after the separation of the liquid material was processed in order to recover the firmly attached microbes (i.e., sample denoted "FG"), as previously described (37). The grass was washed with basal anaerobic (BA) medium (38) to remove loosely attached microbial cells. After this step, the firmly attached microbes were stripped off by incubating the grass at 4°C in anaerobic conditions with BA medium containing 0.15% Tween 80 and, subsequently, by homogenizing the grass with a VDI-12 homogenizer (2 ϫ 2 min bursts; VWR, Radnor, PA).…”
Section: Methodsmentioning
confidence: 99%
“…All the enhanced processes showed higher biogas yields and higher destruction of pathogens than conventional processes. Bassani et al (2016) proposed an innovative system for in-situ conversion of carbon dioxide in the biogas into methane. Through liquid and gas recirculation and chamber configuration, gas-liquid mass transfer was increased.…”
Section: Process Methodology and Technologymentioning
confidence: 99%